PENGGUNAAN MODEL INDEKS TUNGGAL DALAM MENILAI RESIKO DAN RETURN SAHAM UNTUK PILIHAN BERINVESTASI - Anny Widiasmara; Putri Widyasari (Universitas PGRI Madiun, 2017)
ABSTRACTThe purpose of this study was to assess the risk and return stock that could be an option to invest by using single index model Compass 100 on the IDX in 2010-2014. This type of research used in this research is descriptive quantitative approach. Samples taken as many as 44 companies of the index Compass 100. The results showed that of the 44 samples selected companies, there were 13 companies that have an optimal return and minimal risk to the proportion of each stock: UNVR of 0.2372039%, ANTM of 0.0057649% , BMTR of 0.14997799%, GGRM of 0.1226567%, MNCN of 0.1571756%, JSMR of 0.2749157%, KLBF of 0.0493033%, CPIN at 98.771899%, CTRA of 0.1009368%, GJTL of 0.0607808%, MEDC of 0.0209188%, KIJA of 0.0253161%, LPKR 0.0231518%. Based on the portfolio has been formed on the calculation of portfolio return of 4.74% and the risk of a portfolio of 0.0019683%.Keywords : Singe Index Model, Optimal Portfolio, Investment Options